2006
DOI: 10.1242/dev.02179
|View full text |Cite
|
Sign up to set email alerts
|

The centrosome-nucleus complex and microtubule organization in theDrosophilaoocyte

Abstract: Molecular motors transport the axis-determining mRNAs oskar, bicoid and gurken along microtubules (MTs) in the Drosophila oocyte. However, it remains unclear how the underlying MT network is organized and how this transport takes place. We have identified a centriole-containing centrosome close to the oocyte nucleus. Remarkably, the centrosomal components, ␥-tubulin and Drosophila pericentrin-like protein also strongly accumulate at the periphery of this nucleus. MT polymerization after cold-induced disassembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
133
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(149 citation statements)
references
References 48 publications
15
133
1
Order By: Relevance
“…The precise organization of microtubules in Drosophila oocytes has long remained unclear and controversial. One reason for this might be a rapid turnover or rearrangement of microtubules in Drosophila oocytes (Januschke et al, 2006). Using live imaging of fluorescently labeled transcripts, Zimyanin et al (2008) demonstrated that oskar mRNA particles localize to the posterior via a posteriorly biased random walk, using a microtubule network that is only weakly polarized along the anteriorposterior axis.…”
Section: Discussionmentioning
confidence: 99%
“…The precise organization of microtubules in Drosophila oocytes has long remained unclear and controversial. One reason for this might be a rapid turnover or rearrangement of microtubules in Drosophila oocytes (Januschke et al, 2006). Using live imaging of fluorescently labeled transcripts, Zimyanin et al (2008) demonstrated that oskar mRNA particles localize to the posterior via a posteriorly biased random walk, using a microtubule network that is only weakly polarized along the anteriorposterior axis.…”
Section: Discussionmentioning
confidence: 99%
“…Steinhauer, unpublished data). ␥-tubulin isoforms also have been found associated with the oocyte nucleus, and one very recent study hypothesized that the oocyte nucleus is the primary locus of MT nucleating activity in the oocyte (Januschke et al, 2006). In that study, complete depolymerization of oocyte MTs followed by short recovery periods revealed that at stage 9, oocyte MTs regrow from a site at the dorsal anterior corner, near the oocyte nucleus.…”
Section: The Mechanism Governing Mt Organization In the Midoogenesis mentioning
confidence: 92%
“…As a result, it was hypothesized that the posterior MTOC established at stage 2 persists aberrantly after stage 7 in grk mutants (Roth et al, 1995). Januschke et al (2006) propose an alternate model, whereby the posteriorly positioned oocyte nucleus is responsible for the high concentration of posterior MTs in grk mutant oocytes. However, this alternate model cannot account for the aberrant MTs at the posterior of the oocyte in other mutant backgrounds, e.g., in PKA mutants, in which nuclear migration to the dorsal anterior corner occurs normally (see below).…”
Section: Grk Signaling From the Oocyte To The Posterior Follicle Cellmentioning
confidence: 99%
“…The MTs form loose, long parallel bundles perpendicular to the anterior-posterior axis of the oocyte, close to the egg cortex [Januschke et al, 2006]. Most of the cytoplasm components travel along the bundles with a seemingly smooth movement with no mayor changes in direction and velocity.…”
Section: Lipid Droplets In the Developing Egg Primordiamentioning
confidence: 99%
“…The MTs become depolymerized during incubation on ice and form again once the egg primordia are transferred onto to 258C [Januschke et al, 2006]. Imaging of one early stage 12 oocyte per preparation was done in every minute, as described above.…”
Section: Motion Of the Lipid Droplets Is Mt-dependent (A-f) Time Pmentioning
confidence: 99%